Urinary Metabolomics of Plastic Manufacturing Workers: A Pilot Study - Michele De Rosa; Ottavia Giampaoli; Adriano Patriarca; Federico Marini; Antonio Pietroiusti; Lorenzo Ippoliti; Agostino Paolino; Andrea Militello; Anna Rita Fetoni; Renata Sisto; Giovanna Tranfo; Mariangela Spagnoli; et al. (Journal of Xenobiotics)
The plastic manufacturing industry has a crucial role in the global economy with a significant impact in a wide range of fields. The chemical risk to which workers are potentially exposed is difficult to characterize and strictly related to both the products and processes adopted. Among the chemicals used, we can cite styrene, phenol, butadiene and phthalates, but nano- and microplastic particles can also be released in the work environment. In this pilot study, we present for the first time an NMR-based metabolomic approach for assessing urinary profiles of workers employed in a plastic manufacturing company. Urine samples from twelve workers and thirteen healthy volunteers were collected and analyzed by NMR spectroscopy. Forty-six urinary metabolites belonging to different chemical classes were univocally identified and quantified. The dataset so obtained was then subjected to multivariate statistical analysis to characterize each profile and highlight any differences. An alteration in some metabolites involved in several pathways, such as amino acid metabolism and NAD metabolism, was found, and a strong impact on gut microflora was also speculated. Ultimately, our work has the objective of adding a tile to the knowledge of biological effects possibly related to occupational exposure even if it is below the threshold limit values.